Extending the Scope of the Aza‐Fischer Synthesis of 4‐ and 6‐Azaindoles. Issue 16 (15th April 2013) - Thomae, David; Jeanty, Matthieu; Coste, Jérome; Guillaumet, Gérald; Suzenet, Franck
Abstract: Fischer indole cyclization has recently been described as an efficient approach to the synthesis of azaindoles bearing electron‐donating groups. We now show that this cascade reaction can be very efficient for the formation of a wider range of 4‐ and 6‐azaindoles by using microwave irradiation. Abstract : Fischer indole cyclization starting from aminopyridines is a very efficient cascade sequence leading to 4‐ and 6‐azaindoles. The scope of the substituents on the pyridine ring was extended to include halogens and to weakly electron‐donating substituents by using microwave irradiation.